Fujimori’s syndrome - Nizama V., Martin (2009)
The historical precedents of the prosecution of the ex president Alberto Fujimori it is described. He was extradited from Chile surprisingly, after 7 years of his fled in Japan, where he resigned by fax to the presidency of the Republic. The synopsis of the mega-judgment is shown, the theory of the mediator that stated both the extradition and the first sentence of the Magistrate’s court (which established that the murder of the 25 people) were political crimes against humanity and that Fujimori was the master planner. In the psychodynamics the convergence of the narcissistic perversion and the paranoid imbalance is established, as well as the identification of the victim with the aggressor. The victim, the people addicted to Fujimori, their executioner which daughter Keiko is the favorite candidate to the presidency of this eluded electorate. Therefore, in the Fujimori syndrome we can spot the clinic phenomenology observed in Fujimori and his inner circle before, during and after the historic mega-judgment. It is concluded that the Fujimori henomenon is a morbid process that affects the mental health of the Peruvian people and preventive-emotional alternatives are suggested to deal with it.